Modeling and Control of Solar PV with Battery Energy Storage for Rural Electrification - Masenge, Irene H.; Mwasilu, Francis (Tanzania Journal of Engineering and Technology, 2020)
In rural areas where electric power grid network is rarely available, power generation from renewable energy resource such as solar photovoltaic (PV) is mostly accomplished in standalone mode. The standalone solar PV system requires energy storage device to achieve reliable power supply to the end users. This paper presents modelling and coordination control of solar PV with battery energy storage system (BESS) for rural-electrification applications. The proposed control is accomplished via a bidirectional buck-boost converter with the objective of maintaining voltage at the DC bus constant. Simulation results based-on MATLAB/Simulink platform confirms good performance of the proposed system. Keywords: Photovoltaic (PV), Energy Storage System (ESS), Maximum Power Point Tracking (MPPT)